Strategi Efektif Program Bimbingan Dan Konseling Dalam Meningkatkan Kehadiran Siswa - Rospa; Tri Yuni Hendrowati; M. Badrun (Universitas Muhammadiyah Surakarta, 2025)
This research aims to explore and identify effective strategies within the guidance and counseling (BK) program that can enhance student attendance rates at SMA Negeri 2 Kotaagung. In the educational context, student attendance is a crucial indicator of academic success and character development. By exploring collective wisdom from various sources, this research aspires to contribute to the development of more relevant and impactful BK programs. The study employs a qualitative approach using a case study method, involving in- depth interviews, observations, and document analysis related to the implementation of the BK program. The findings reveal that active student engagement in the BK program, increased family support, transportation services, fostering a passion for learning, bullying prevention, and school health services are effective strategies in improving student attendance. Moreover, the use of technology, such as attendance monitoring applications, is also acknowledged as a critical element in supporting the program’s success. The research also uncovers that collective wisdom, involving teachers, counselors, parents, and students in creating an inclusive and supportive school environment, is a key factor in enhancing student motivation and commitment to attending school consistently.